Cover Picture: Carbonylation of Csp3−H Bonds through Oxidative Wittig‐Type Reaction: An Unprecedented Version of Wittig Reaction (Asian J. Org. Chem. 5/2016). Issue 5 (26th April 2016) - Zhu, Yingzu; Lü, Shiwei; Ma, Xingge; Zhang, Liang; Luo, Liangliang; Jia, Xiaodong
Abstract : An oxidative Wittig‐type reaction was developed. The classical Wittig reaction is one of the most powerful synthetic tools for construction of carbon–carbon double bonds from carbonyls, but here comes a surprising version, in which carbonyl groups are installed by similar process. The mechanism shows that the reaction is mediated by an oxo‐four‐membered intermediate, which looks like a humorous face. More information can be found in the communication by X. Jia and co‐workers onpage 617 in Issue 5, 2016 (DOI:10.1002/ajoc.201600055 ).